TRANSFORMATIONAL LEADERSHIP ON JOB SATISFACTION AMONG REGISTERED NURSES CARING PERSPECTIVE: A SYSTEMATIC REVIEW - Vallejo, Elizabeth; Borrico, Carlo Bryan (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: The healthcare profession face scarcity due to increased global demand for registered nurses. The inadequacy of the healthcare workforce is a critical concern in an organization, as it is difficult to retain and recruit qualified staff to deliver safe and quality outcomes in the provision of care. Numerous studies identify transformational leadership style as an effective style to foster job satisfaction among licensed nurses. Objective: The study aimed to review transformational leadership in relation to job satisfaction according to Registered Nurses perspective. Design: This systematic review utilized the Cochrane Collaboration procedures and PRISMA statement. Data source: A comprehensive search of Pubmed, CINAHL, ScienceDirect, Cochrane Library, Wiley Online, and Google Scholar published from 2018 to 2023. Ten articles of cross-sectional studies met the inclusion criteria. Review Methods: The method utilized is the JBI Critical Appraisal Checklist for Analytical Cross-Sectional Studies. Results: All articles demonstrated that a transformational leadership style was reported to have a positive correlation among registered nurses' job satisfaction. In addition, four main themes emerged to determine job satisfaction variables on organizational commitment, work environment, competencies in evidence-based practices, and resilience of skilled nurses to minimize the repercussions of the inadequacy of nurses in the healthcare setting. Conclusion: Transformational leadership contributes to improving job satisfaction and instituting the identified themes that could support the development of caring strategies that would close the gap of registered nurses’ shortage in healthcare.